2008
DOI: 10.1637/1933-5334(2008)3[e7:meocav]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Epidemiology of Chicken Anemia Virus (CAV) in Southeastern Chinese Live Birds Markets

Abstract: Reg BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 0 publications
2
5
0
Order By: Relevance
“…The overall phylogenetic pattern and clustering of different CAV isolates based on the partial VP1 gene in this study was similar to previous one based on complete sequence of VP1 gene [ 24 ] or the entire CAV genome [ 25 ] for the common CAV isolates considered in all the three studies. This suggests that relationships of different CAV isolates can be determined on the basis of partial sequence of VP1 gene due to the fact that most of the amino acid substitutions in comparisons between isolates lies in VP1 gene and more specifically on the N-terminal half of VP1 gene.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The overall phylogenetic pattern and clustering of different CAV isolates based on the partial VP1 gene in this study was similar to previous one based on complete sequence of VP1 gene [ 24 ] or the entire CAV genome [ 25 ] for the common CAV isolates considered in all the three studies. This suggests that relationships of different CAV isolates can be determined on the basis of partial sequence of VP1 gene due to the fact that most of the amino acid substitutions in comparisons between isolates lies in VP1 gene and more specifically on the N-terminal half of VP1 gene.…”
Section: Discussionsupporting
confidence: 84%
“…This is similar to the result by Ducatez et al . [ 24 ] where they indicated a very slow CAV virus evolution at amino acid level corresponding to a strong negative selection (0.04 to 0.20) of VP1 gene in China and worldwide. However, in this study, we found that one of the isolates has omega value of 0.50 meanwhile five out of 12 isolates have omega value between 0.25 to 0.35 and the rest with omega value of 0.07 to 0.11 (Table 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Genetic characterization of numerous Lao CoV and CAV strains from chickens and ducks was attempted. Almost all Lao strains were closely related to strains from Asia, but, as observed previously (Ducatez et al, 2008;Valastro et al, 2016), the phylogenetic analyses revealed no clear geographic clustering. Most interestingly, the partial genomes from virus strains detected in ducks and chickens were closely related, which further highlights the high risk of cross-species transmission in this setting.…”
Section: Discussionsupporting
confidence: 47%
“…We therefore applied a generic PCR allowing the detection of CoV strains from all genera. The highly variable VP1 gene of CAV, which is also a major genetic determinant of virulence, has been the target of many studies assessing the genetic diversity of CAV strains (Renshaw et al, 1996;Yamaguchi et al, 2001;Ducatez et al, 2006;Ducatez et al, 2008;Hailemariam et al, 2008;Snoeck et al, 2012;Li et al, 2017). In addition, all samples were tested for NDV by real-time RT-PCR (Mia et al, 2008) targetting the matrix gene.…”
Section: Virus Screening and Sequencingmentioning
confidence: 99%
“…CAV was detected by PCR in the examined broiler flock and the amplified PCR product, which represent partial VP1 gene, was sequenced and the CAV strain was designated as CLEVB-Zag2 with accession number KX171350 at the gene bank. Phylogenetic analysis at the amino acids and nucleotide level of VP1 classify CLEVB-Zag2 CAV under group III (Genotype III) of the CAV in agreement with Islam et al (2002), Ducatez et al (2006Ducatez et al ( , 2008, Craig et al (2009), Kim et al (2010) and Snoeck et al (2012).…”
Section: Discussionmentioning
confidence: 68%